Incidence and Clinical Features of Urethral Injuries with Pelvic Fractures in Males: A 6-Year Retrospective Cohort Study at a Single Institution in South Korea - Hyun Woo Sun; Hohyun Kim; Chang Ho Jeon; Jae Hoon Jang; Gil Hwan Kim; Chan Ik Park; Sung Jin Park; Jae Hun Kim; Seok Ran Yeom (Journal of Trauma and Injury)
Purpose Severe pelvic fractures are associated with genitourinary injuries, but the relationship between pelvic trauma and concomitant urethral injuries has yet to be elucidated. This study evaluated the incidence, mechanism, site, and extent of urethral injuries in male patients with pelvic fractures. Methods A retrospective cohort study was performed involving patients with urethral injuries accompanying pelvic fractures who visited Pusan National University Hospital from January 1, 2014 to December 31, 2019. Demographics, mechanisms of injury, clinical features of the urethral injuries, concomitant bladder injuries, methods of management, and the configuration of the pelvic fractures were analyzed. Results The final study population included 24 patients. The overall incidence of urethral injury with pelvic fracture was 2.6%, with the most common mechanism of urethral injury being traffic accidents (62.5%). Complete urethral disruption (16/24, 66.7%) was more common than partial urethral injuries (8/24, 33.3%), and unstable pelvic fractures were the most common type of pelvic fracture observed (70.8%). There was no definitive relationship between the extent of urethral injury and pelvic ring stability. Conclusions The present study provides a 6-year retrospective review characterizing the incidence, mechanism, and clinical features of urethral injury-associated pelvic fractures. This study suggests that the possibility of urethral injury must be considered, especially in unstable pelvic fracture patients, and that treatment should be chosen based on the clinical findings.